Osmanlı Sarayları'nda dış mekan tasarımı üzerine bir değerlendirme: Dolmabahçe ve Yıldız örnekleri - Kaşif, Burcu (İstanbul Kültür Üniversitesi / Fen Bilimleri Enstitüsü / İç Mimarlık ve Çevre Tasarımı Anabilim Dalı, 2010)
Bu araştırmada, Osmanlı tarihi boyunca Osmanlı Saray bahçelerinde etkili olan peyzaj sanatları, Osmanlı Sarayları ve dış mekân tasarımları incelenerek Osmanlı'nın dış mekân tasarım anlayışındaki gelişim ortaya konmuştur. Dünyada moda olmuş ve geç dönem Osmanlı Saray bahçelerinin tasarımında etkili olan peyzaj sanatlarının Osmanlı'nın geleneksel tasarım anlayışıyla birleşerek yeni bir sentez oluşturduğu Dolmabahçe ve Yıldız Sarayı örnekleri ayrıntılı biçimde ele alınmış ve geç döneme ışık tutulmuştur. Tez beş bölümden oluşmaktadır. Giriş bölümünde ilk olarak ?Dış Mekân? ve ?Bahçe? kavramları tanımlanmış, yarar sağlama ilkesinden doğan bahçe kavramının estetik anlayışa göre biçimlenen, zevk ve huzur veren doğa parçalarına dönüşüm süreci üzerinde durulmuş ve ?Bahçe? kelimesinin etimolojik yapısı araştırılmıştır. Daha sonra araştırmanın ne amaçla yapıldığı, kapsamı ve çalışma yöntemi anlatılmıştır. İkinci bölümde Klasik Osmanlı Sarayları'nın ve Batı etkisindeki Osmanlı Sarayları'nın dış mekân tasarımında etkili olan peyzaj sanatları ayrıntılı biçimde ele alınmıştır. Bu sanat akımlarının ortaya çıkışı ve gelişim süreci örneklerle anlatılmış, genel planlama özellikleri belirtilmiştir. Üçüncü bölümde Osmanlı Sarayları'nda dış mekân tasarımının tarihsel gelişim süreci anlatılmıştır. Öncelikle Osmanlı'da bahçe anlayışına değinilmiştir. Osmanlı padişahlarının doğaya duydukları saygı, bahçeye, çiçeğe, meyveye verdikleri önem belirtilmiş, bahçe ve bostan işleri için kurulan Bostancı Ocağı'nın özellik ve görevlerinden bahsedilmiştir. Dış mekân tasarımının tarihsel gelişim süreci Erken Dönem, Klasik Dönem, Geç Dönem başlıkları altında ele alınmış, dönemin dış mekân planlama özellikleri anlatılmış, Osmanlı'ya başkentlik yapmış Bursa, Edirne ve İstanbul'da inşa edilen saray ve bahçeleri sırasıyla ele alınmıştır. Dördüncü bölümde Geç Dönem Osmanlı Sarayları'ndan Dolmabahçe ve Yıldız Sarayları'nın dış mekân tasarımları ayrıntılı biçimde incelenmiş bu dönemde etkili olan Rönesans, Fransız Barok ve İngiliz Naturalistik peyzaj sanatlarının bu bahçelerdeki yansımaları anlatılmıştır. Son bölümde Erken Dönem Sarayları'ndan başlayarak Son Osmanlı Saray'ına kadar dış mekân tasarımlarının karşılaştırmalı analizi yapılmıştır.

In this study, the development of the Ottoman exterior design concept was revealed by examining the landscape arts effective on the Ottoman gardens throughout the history of Ottoman, the Ottoman palaces and the exterior designs of the palaces. As the samples of a new synthesis, created by the combination of worldwide fashionable landscape arts effective on the late Ottoman palace garden designs and the traditional Ottoman design concept, Dolmabahce and Yildiz palaces were covered in detail and the late Ottoman palace garden designs were shed light on. This thesis consists of five sections. The introductory chapter of the thesis at first, after defining concepts of ?Exterior Space? and ?Garden?, the transformation process of the concept of ?Garden? arising from the policy of providing benefits to pieces of nature of pleasure and peace was focused on as based on the idea of aesthetics, and the word of ?Garden? was examined etymologically. Subsequently, provides the purpose, scope and working methods of the research. The introductory chapter of the thesis at first provides the purpose, scope and working methods of the research. Subsequently, after defining concepts of ?Exterior Space? and ?Garden?, the transformation process of the concept of ?Garden? arising from the policy of providing benefits to pieces of nature of pleasure and peace was focused on as based on the idea of aesthetics, and the word of ?Garden? was examined etymologically. In the second section, the landscape arts which have an impact on the exterior designs of the classical Ottoman Palaces and the Ottoman Palaces under Western influence were discussed in detail. Furthermore, the emergence and the development process of the landscape art movements were explained with examples and the general plan features of the aforesaid art were also expressed. In the third section, the historical development process of the Ottoman Palace exterior design was described. The Ottoman garden concept was referred primarily in this section. The Ottoman Sultans? respects to the nature and the importance that they gave to gardens, flowers, and fruits were explained and the ?Bostancı Ocağı? - established specifically for gardening and orcharding- with its specified features and functions was also mentioned. Additionally in this section, the historical development process of exterior designs was covered under the titles of Early Period,Classical Period and Late Period with the outdoors planning features of these periods while the palaces and gardens built in the capitals of Ottoman Empire, namely Bursa, Edirne and Istanbul, were addressed consecutively. In the fourth section, the exterior designs of the late Ottoman palaces Dolmabahce and Yildiz were examined in detail and the reflections of Renaissance, French Baroque and English Naturalistic landscape arts, influential art trends of the time, on the gardens of aforementioned palaces were described. In the last section, the analysis of exterior designs starting from the early period to the last Ottoman palaces was made comparatively.
An assesment on the exterior designs of the Ottoman Palaces through the models of Dolmabahce ve Yildiz
Keywords: landscape architecture; peyzaj mimarlığı